Ancestors of Worthy Life : Plantation Slavery and Black Heritage at Mount Clare - Moyer, Teresa S., 1976- (Book collections on Project MUSE., 2015)
America plantation sites are reluctant to show and interpret the homes and lives of the slaves that used to reside there in times of slavery. Mount Clare is one such site and Teresa Moyer examines the lives of its former slaves and the issues keeping these findings hidden. Raising questions about how race continues to affect the decisions made at historic sites, Moyer discovers that slaves at Mount Clare adopted the ceremonies of their owners while still exercising their freedoms of family and homeland culture.